The Meaning of the Village Legend in the Collective Memory of the Bugis Community of Maccile Village, Lalabata District, Soppeng Regency - Ria Ayunita; Andi Agussalim AJ (Panrita: Jurnal Bahasa dan Sastra Daerah serta Pembelajarannya, 2021)
The Meaning of the Village Legend in the Collective Memory of the Bugis Community of Maccile Village, Lalabata District, Soppeng Regency. Regional Language and Literature Education Study Program, Department of Indonesian Language and Literature, Faculty of Language and Literature, Makassar State. This study aims to (1) find out the meaning of the village legend icon in the collective memory of the Bugis community, Maccile village, Lalabata district, Soppeng district (2) find out the meaning of the village legend index in the collective memory of the Bugis community, Maccile village, Lalabata district, Soppeng district (3) find out the meaning of the village legend symbol. in the collective memory of the Bugis community, Maccile Village, Lalabata District, Soppeng Regency. This type of research is qualitative research. This research was conducted in Maccile Village, Lalabata District, Soppeng Regency. The research was conducted in June – August 2021. The techniques used to obtain data in this study were interview techniques and documentation techniques. The techniques used to analyze the data are: data reduction, data presentation, and data retrieval. The results of this study note that the meaning of the legend of the name of the village in Maccile Village is the meaning of the icon, index, and also the meaning of the symbol, one of which is Maccile. with flowing water, then the meaning of the index in Maccile's name is a natural phenomenon in which the spring seeps in the sense of flowing, the name Maccile is associated with the name of the cleric named I Chile, while the meaning of the symbol in Maccile is the name of the cleric, namely I Chile and the water seeps in the sense of flowing.